Chlamydial infection in a high risk population: association with vaginal flora patterns - Marconi, Camila [UNESP]; Donders, Gilbert G. G.; Martin, Laura F. [UNESP]; Ramos, Bruna R. A. [UNESP]; Duarte, Marli Terezinha Cassamassimo [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP]; Tristao, Andrea R.; Silva, Marcia Guimarães da [UNESP] (Springer Heidelberg, 2012)
This study aimed to determine the frequency of Chlamydia trachomatis (CT) infection among high risk Brazilian women and evaluate its association with vaginal flora patterns.This was a cross-sectional study, performed in an outpatient clinic of Bauru State Hospital, So Paulo, Brazil. A total of 142 women were included from 2006 to 2008. Inclusion criteria was dyspareunia, pain during bimanual exam, presence of excessive cervical mucus, cervical ectopy or with three or more episodes of abnormal vaginal flora (AVF) in the previous year before enrollment. Endocervical CT testing was performed by PCR. Vaginal swabs were collected for microscopic assessment of the microbial flora pattern. Gram-stained smears were classified in normal, intermediate or bacterial vaginosis (BV), and recognition of Candida sp. morphotypes. Wet mount smears were used for detection of Trichomonas vaginalis and aerobic vaginitis (AV).Thirty-four of 142 women (23.9%) tested positive for CT. AVF was found in 50 (35.2%) cases. The most frequent type of AVF was BV (17.6%). CT was strongly associated with the presence of AV (n = 7, 4.9%, P = 0.018), but not BV (n = 25, 17.6%, P = 0.80) or intermediate flora (n = 18, 12.7%, P = 0.28).A high rate of chlamydial infection was found in this population. Chlamydia infection is associated with aerobic vaginitis.
Keywords: Chlamydia trachomatis; Bacterial vaginosis; Aerobic vaginitis; Vaginal flora; PCR